BAHASA UNGKAPAN DALAM PERTUNJUKAN WAYANG KULIT SEBAGAI CERMIN PANDANGAN HIDUP - Tatik Harpawati; Jaka Rianto (Institut Seni Indonesia Surakarta, 2012)
Expression language is a product of Javanese culture. Therefore, the expression for the Java language is a reflection of local wisdom . Expression language in the realm of Javanese literature has variations designations, such proverbs, peribahasan, bebasan, saloka, and pepindhan. Expression language in the Wayang indeed a product so as to interpret the Javanese to be seen by the Javanese worldview. The use of the expression language puppet show scattered in chess (Janturan, pocapan, and ginem). The problem in this article, namely how to form a language expression, functions, and values of life contained therein. The goal is to describe, an explanation of the expression language function, and get an explanation of the values of life contained therein. Based on the key word metaphors, expression language in the Wayang classified into eight types, namely: animals, plants, people, body parts, relatives, things in heaven, things in earth, and water. Based on the study of the meaning of the obtained results that address how people live in harmony with family, friends, community, neighborhood, country, and God. Different outlook on life is packaged in the form of language and expression when applied in chess puppet show that will add weight to the aesthetic presentation. Key words : expression language, puppet show, the value of life